Faktor- Faktor Yang Mempengaruhi Produksi Jeruk Di Desa Punten Kecamatan Bumiaji Kota Batu - Wulan, Wulan Puspitasari; M Zul Mazwan (Jurnal Ekonomi Pertanian dan Agribisnis, 2026)
This study aims to determine the factors that affect orange production in Punten Village, Bumiaji District, Batu City. The population was selected by purposive sampling, namely orange farmers who previously planted apples and then switched to oranges. From a total population of 240 farmers, 36 respondents were selected through random sampling. The analysis method used was the Cobb-Douglas production function. The independent variables include land area (m3), seedlings (trees), labor (working days/HOK), organic fertilizer (kg), inorganic fertilizer (kg), liquid pesticide (milliliters), and herbicide (milliliters), while orange production is the dependent variable. The results showed that land area had a significant positive effect on production. Inorganic fertilizer had a significant negative effect, while labor, seedlings, liquid pesticides, organic fertilizers, and herbicides did not have a significant effect on orange production in Punten Village, Bumiaji District. An increase in land area by 1 m3 will increase the orange harvest by 1,024 kg. On the other hand, the addition of 1 kg of inorganic fertilizer decreased production by 0.101 kg, indicating that excessive inorganic fertilizer application decreased soil fertility. Adding or reducing labor by 1 working day (HOK) did not affect production, as did adding or reducing one seedling. Likewise, variations in the volume of liquid pesticides, organic fertilizers, or herbicides did not have a significant impact on orange yields in Punten Village, Bumiaji District, Batu City.   Keywords: Coub Doglass production function, production factors, orange business, production